Gaya Kepemimpinan Partisipatif Kepala Sekolah dalam Peningkatan Profesionalisme Pendidik serta Tenaga Kependidikan: The Principal's Participatory Leadership Style in Improving the Professionalism of Educators and Education Personnel - Zahrotul Mufidah; Nunuk Hariyati; Wiwin Yulianingsih (ITScience (Information Technology and Science), 2025)
Participatory leadership is gaining increasing attention in the educational context, as this leadership style involves the active participation of team members in decision-making and planning, which is essential for creating a productive school climate. This study aims to examine the role and impact of participatory leadership by principals in improving teacher professionalism. Using a qualitative approach through a literature review method, this study collected and analyzed various relevant sources on participatory leadership in education. The results indicate that principals who implement participatory leadership can create an environment that supports teacher professional development. Involving teachers in decision-making, encouraging open communication, and facilitating close collaboration between principals and staff have been shown to improve teacher professionalism. Furthermore, this leadership style provides teachers with space to develop independently, increasing their motivation and engagement in the learning process, and ultimately enhancing the quality of teaching in schools. This study also found that implementing participatory leadership requires a strong commitment from principals in building a collaborative and inclusive school culture. These findings contribute to the development of more effective and relevant education policies, particularly in improving the quality of education through teacher empowerment. Therefore, this study can provide important insights for education policies and the implementation of more adaptive and collaboration-based leadership.